Kesiapan Memimpin Generasi Milenial: Kajian Kompetensi Karyawan Divisi SDM - Muhammad Takrim; Shalahuddin Shalahuddin; Muhamad Yusup (Studi Ilmu Manajemen dan Organisasi, 2024)
Purpose: The study aims to determine the readiness of leaders in leading millennial employees, focusing on the competencies of Human Resources (HR) division employees. This research is significant due to the critical nature of millennials, making it necessary for leaders to be well-prepared to effectively guide them.Methodology: This research adopts a qualitative descriptive analysis approach through a literature review. The data were obtained from active employees in companies located in Bekasi and surrounding areas. The study examines leadership styles and competencies such as motives (ability to motivate), traits (ability to direct), self-concept (personal concepts), knowledge, and skills.Results: The findings, based on responses from 98 employees in the HR division in companies around Bekasi, show a high level of leader readiness for decision-making, with 59.2% of respondents agreeing that their leaders consistently seize opportunities. Additionally, leaders' human relation skills are rated highly, with 61.2% of respondents strongly agreeing that their superiors exhibit goodwill, fairness, respect, and appreciation for others. Lastly, in terms of knowledge competency, 57.1% of respondents agree that their leaders possess the knowledge necessary to complete tasks in any situation.Conclusions: The readiness of leaders to lead the millennial generation is relatively high, especially in terms of decision making, human relations skills, and knowledge competencies.Limitations: The study focuses only on companies in the Bekasi region and may not represent the readiness of leaders in other areas. The research is also limited to the HR division and does not explore other functional departments, which may have different leadership dynamics.Contribution: This research contributes to the understanding of leadership readiness in managing millennial employees, particularly in the HR division. It highlights critical leadership competencies and offers insights for organizations looking to improve their leadership strategies in dealing with millennials, providing valuable input for leadership development programs in the HR sector.